Effectiveness Of Giving Biscuits To Increase Body Mass Index (Bmi) And Interpretation Of Fetal Weight In Pregnant Women Chronic Energy Deficiency - Damayanti .; Sri Julia Ningsih; Tati Murni Karo Karo; Siti Sarah Bintang (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Supplemental Feeding (PMT) is a program launched by the government to improve the nutrition of pregnant women. The prevalence of pregnant women with chronic energy deficiency problems in developing countries ranges from 15-47% with a BMI of <18.5. The country with the highest prevalence is Bangladesh at 47%. While Indonesia became the fourth largest after India with a prevalence of 35.5%. The purpose of this study is to find out the effect of PMT biscuits on the increase in the body index of pregnant women and the interpretation of fetal weight in pregnant women with chronic energy deficiencies in the working area of Puskemas Sei Suka district Sei Suka Batu Baru District in 2021. The design of this research is quantitative with an experimental quasi approach. The population in this study is all pregnant women with chronic energy deficiency Sampling techniques use consecutive sampling where the sample is taken if it meets the criteria. Data analysis using Paired Sample T Test analysis The results of the study obtained a significant influence on the administration of PMT biscuits on the increase in BMI of pregnant women with a value of p = 0.001 and interpretation of fetal weight (IFW) p = 0.0001 had a significant influence (p < 0.05). From the results of research, the provision of PMT in pregnant women can increase for the mother and the fetus through the interpretation of fetal weight but must be with close supervision, this is due to the attitude of mothers who do not consider the important pattern of weight gain of pregnant women but also there is a sense of boredom in the taste. In the results of the study it can be concluded that the administration of PMT biscuits can improve the welfare of the mother and fetus.